Interethnic Relationships and Migration Process at the Regional Level: Problems and Main Trends of Development - Krestyanova, Lyubov Sabirdzyanovna (Economy of Regions, 2016)
The article is devoted to the problems and trends of the development of interethnic relationships at the regional level. The assumption that migration process has direct influence upon them is proved. The hypothesis of the research is that the interethnic relationships of “traditional” ethnic communities for the region fundamentally differ from the interethnic relationships of the ethnic communities formed by the new migrants. For the first ethnic communities, ethnicity is not so important while the civil identity is more relevant and over-ethnic integrated images are developed. That results in the reduction of interethnic tension. For the other ethnic communities, ethnic and cultural barriers are strong, ethnicity is relevant for them. Furthermore, the language curtain and social distance strengthen interethnic tension for these ethnic communities. In our opinion, the basic threat is that the efforts of public authorities for the harmonization of interethnic relationships are mainly bending to the first ethnic communities. The public authorities attempt to save and develop the ethnic culture to form tolerance. Meanwhile, the major interethnic tension is associated with the migration process, a negative perception of migrants and a number of socio-psychological problems. Main factors having the influence on the negative perception of migrants and interethnic tension are analyzed. The conclusions are based on the research conducted by the author in 2011, relying on the questionnaire and expert survey, on the research conducted from 2008 till 2015, on the analysis of national population census and analytical reviews about migration situation. The results of the study can be used by the public authorities of the region developing ethnic policy, migration policy in formulation forecast of socio-economic development and social tension.